Effectiveness of animal-assisted therapy on pain in children: A systematic review and meta-analysis - Yuanyuan Zhang; Fanghong Yan; Sijun Li; Yutan Wang; Yuxia Ma (Elsevier, 2021)
Aims: Animal-assisted therapy (AAT) relieves pain by creating a relaxed and comfortable environment to reduce anxiety in children. Yet little is known about its effects on pain in children. This study aims to systematically evaluate the effects of AAT on pain in children. Methods: Eight databases including PubMed, Cochrane Library, Web of Science, CINAHL Complete, Chinese Biomedical Database (CBM), Weipu Database (VIP), China Knowledge Resource Integrated Database (CNKI) and Wanfang Database were retrieved, and all randomized controlled trials or controlled clinical trial using AAT on children's pain were recruited from inception to October 2019. Two reviewers independently screened literature, extracted data and assessed the risk of bias of the included studies. RevMan 5.3 software was employed for meta-analysis. Results: Seven published studies containing 4 RCTs and 3 CCTs were included for the systematic review. The results of meta-analysis showed that AAT could reduce children's pain when compared with the control group [MD = −0.53, 95% CI (−0.77, −0.30), P < 0.00001]. Conclusion: Current evidence shows that AAT can relieve pain in children to some extent. Considering the limited quality and quantity of the available studies, more high quality studies should be performed to verify the above conclusion.